Perception of understanding COVID-19 among doctors at Patan Hospital, Nepal - Pandey, Bimal; Lama, Mipsang; Shah, Prashant Kumar; Rajbhandari, Piyush; Sigdel, Keshav; Hirachan, Niroj (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and presents with fever, dry cough, fatigue, myalgia, and dyspnea. This study aims to is find out the understanding of COVID-19 among doctors at Patan Hospital. Method: A cross sectional was conducted among doctors at Patan Hospital, Patan Academy of Health Sciences, Nepal. The questionnaire in Google form consisted, part1 perception on COVID-19 and part2 understanding using multiple choice questions corresponding to the one to fifteen questionnaire in part1. Ethnical approval was obtained. Result: Sixty-one doctors participated in the study, of which 65.5% were directly involved in management of COVID-19. Perception and understanding regarding transmission status in country was 65.6% and 63.95% respectively, about case definition 90.1% and 62.2%, about when to do diagnostic tests 75.4% and 90.2%. Conclusion: There was difference in perception and understanding regarding COVID-19 among doctors, and areas to be reinforced were case definition, transmission classification, diagnostic tests.